Barriers to MSMEs growth and performance in the Free State Province: a focus on DFI funded enterprises - Mokalake, Lemphane Andrew (Graduate School of Business (GSB), 2025)
Micro, Small and Medium-sized Enterprises (MSMEs) are vital for economic development, but they face a number of challenges, including financial exclusion, limited entrepreneurial skills, and regulatory burdens. While financial inclusion is a policy priority, its linkage with the performance of MSMEs remains ambiguous. Development Financial Institutions (DFIs) have shown mixed results, with high loan impairments and insufficient focus on micro and small businesses. This dissertation explores issues of access to finance, managerial skills, and institutional support, among others, as some of the major factors influencing the performance of MSMEs funded by the Free State provincial DFI. This dissertation collected primary data through structured questionnaire from 50 MSME owners to analyse the effect of financial literacy, digital literacy, human capital, post-funding support and MSMEs financial performance. The findings from the regression analysis reveals that, this dissertation identified managerial skills, digital literacy, and human capital are positive determinants for MSME performance, which indicates the importance of leadership, technology adoption, and skilled labour. However, training programmes demonstrate a negative relationship, indicating the gap between training content and practical needs. Post-funding support has turned out to enhance success significantly, emphasising the role of mentorship, advisory services, and capacity building for sustainable growth. Policies can enable the provincial government, banking institutions, and DFIsto improve access to low-cost capital. When used in conjunction with financial literacy courses, they have the potential to help reduce MSME's underperformance and create an enabling business climate. Policies have to target strengthening the capacity, transparency and accountability of finance institutions that extend finance to MSME's. Simplifying process and reducing bureaucracy can enhance the efficiency of institutions. Provincial government needs to launch support schemes that addresses money, management, and market challenges in a holistic way. Literacy programmes have to incorporate field applications and interactive tips to foster skills.